A neglected case of blunt eye injury leading to pediatric cataract: a lifetime consequence case report - Jelly Vianti Fransisca Oeiyano; Raymond Oliver Mantu; Samuel Samatara (Intisari Sains Medis, 2022)
Background: A pediatric traumatic cataract is one of the children's main causes of unilateral visual impairment. It is defined as a permanent opacification of the lens caused by penetrating or blunt trauma to the eye, which might damage the vision. A traumatic pediatric cataract is preventable and treatable. This case study aims to evaluate a neglected case of blunt eye injury leading to pediatric cataracts. Case Description: A 15-year-old boy came with chief complaints of decreased visual acuity in his left eye for the last 2 years. He has a history of blunt eye injury around 3 years prior in the left eye but left untreated. The patient's visual acuity was 1 per light perception in the left eye. An ophthalmologic examination of the left eye showed an opacity in the lens. The posterior segment cannot be examined. The patient was assessed with a traumatic cataract and was planned to be operated on, but the parents refused. Conclusion: Prompt first aid and timely surgical intervention are necessary for optimal results. Parents play a critical role in the patient's prognosis by observing closely after eye trauma and bringing their children to the right medical facility.